DATURA METEL LINNAEUS SEBAGAI INSEKTISIDA DAN LARVASIDA BOTANI SERTA BAHAN BAKU OBAT TRADISIONAL - Mardiana, Mardiana; Supraptini, Supraptini; Aminah, Nunik Siti (Media Penelitian dan Pengembangan Kesehatan, 2009)
Controlling dengue hemorrhagic fever vector would be better when the people could choose their own choice of method such as spraying synthetics insecticide, using abate as synthetics larvacide, using fish as biological controller, and using electrical racket as mechanical controller. Besides, using poisonous plant as alternative controlling method was being encouraged. Datura metel is a wild plant from a mountain area, which could not be eaten, easy to grow, cheap, safe and environmental friendly. Lethal concentration CL50 towards larvae is 0.600 µg, and CL 95 to control Aedes aegypti larvae is 1.250 µg. Al Using extract of "daun kecubung" in 2% or 3% or 4% concentration did not have any effect as insecticide. Datura metel could be used as botanical insecticide and larvacide, yet it could used as traditional remedy for low back pain, flatulent asthma, rheumatoid, eczema, dermatitis, bone pain, fever, and as pain killer for dysmenorrhea.   Key words : Datura Metel, Botanical Insecticide, Traditional Medicine